Uncovering the Potential of Lipid Drugs: A Focus on Transient Membrane Microdomain-targeted Lipid Therapeutics - Schneider Alves, Anna C.; Cardoso, Raquel Soares; de Oliveira Neto, Xisto Antonio; Kawano, Daniel Fábio (Mini Reviews in Medicinal Chemistry, 2022)
Membrane lipids are generally viewed as inert physical barriers, but many vital cellular processes greatly rely on the interaction with these structures, as expressed by the membrane hypothesis that explain the genesis of schizophrenia, Alzheimer's and autoimmune diseases, chronic fatigue or cancer. The concept that the cell membrane displays transient membrane microdomains with distinct lipid composition providing the basis for the development of selective lipid-targeted therapies, the membrane-lipid therapies (MLTs). In this concern, medicinal chemists may design therapeutically valuable compounds 1) with a higher affinity for the lipids in these microdomains to restore the normal physiological conditions, 2) that can directly or 3) indirectly (via enzyme inhibition/activation) replace damaged lipids or restore the regular lipid levels in the whole membrane or microdomain, 4) that alter the expression of genes related to lipid genesis/metabolism or 5) that modulate the pathways related to the membrane binding affinity of lipid-anchored proteins. In this context, this mini-review aims to explore the structural diversity and clinical applications of some of the main membrane and microdomain-targeted lipid drugs.
Keywords: cancer